Foam metal modification method and electro-catalysis application thereof

By performing a two-step modification process of calcination and electroreduction on foam metal, a nanosheet-like surface structure and optimized electronic structure are formed, which solves the problems of insufficient activity and stability of existing foam metal catalysts. This enables efficient and low-cost electrocatalytic reduction of aromatic nitriles, which is suitable for the green preparation of aromatic amines.

CN121065732APending Publication Date: 2025-12-05UNIV OF SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511266210.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-05
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Existing foam metal catalysts exhibit insufficient activity, low selectivity, and poor stability in the electrocatalytic reduction of aromatic nitriles to aromatic amines. Furthermore, traditional modification methods are complex, costly, and difficult to scale up.

Method used

A two-step synergistic modification method of calcination-electroreduction was adopted to form a nanosheet-like surface structure through high-temperature oxidation, exposing more active sites, and to optimize the electronic structure through constant potential electrochemical reduction, thereby improving catalytic performance.

Benefits of technology

It achieves high efficiency, low cost, and high electrocatalytic activity and stability, and is suitable for the green preparation of various aromatic nitriles, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121065732A_ABST
    Figure CN121065732A_ABST
Patent Text Reader

Abstract

The invention provides a foam metal modification method and electro-catalysis application thereof. The foam metal modification method comprises the following steps: A) calcining foam metal; and B) performing electrochemical reduction on the foam metal obtained in the step A) under constant potential to obtain the modified foam metal. According to the method, a synergistic modification strategy of first calcination and then electroreduction is adopted, in the calcination process, the surface of the foam metal is oxidized, directional surface reconstruction is achieved through high-temperature driving, and the nanoscale morphology with high roughness is formed; and in the subsequent electroreduction process, the oxidation-state metal is precisely reduced into a metal simple substance or alloy, and meanwhile, the electronic structure is optimized through potential regulation and control. Through the synergistic effect of the two, the specific surface area of the modified foam metal is remarkably increased, and the number of exposed catalytic active sites is greatly increased, so that the foam metal shows excellent catalytic activity and target product selectivity in a reaction for preparing aromatic amine through electro-catalytic reduction of aromatic nitrile.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a method for electrocatalytic reduction of aromatic nitrile to prepare aromatic amine, in particular to a method for modifying a foamed metal and its application in electrocatalytic preparation of aromatic amine. BACKGROUND

[0002] Aromatic amines, as a class of key organic chemicals, are widely used in the fields of medicine, dye, pesticide and polymer material synthesis. In industrial production, aromatic amines are prepared by direct catalytic hydrogenation of nitriles, which is a mainstream method with cost-effectiveness and atom economy. However, the traditional method of nitrile hydrogenation has obvious limitations: it often needs to be carried out under high temperature and high pressure conditions, and relies on noble metal catalysts such as Pd and Pt, and hydrogen gas as a reducing agent. These characteristics directly lead to high catalyst cost, high energy consumption, harsh operating conditions, and may also cause potential environmental pollution problems. Therefore, it is of great significance to develop an efficient, green and economical method for the reduction of aromatic nitriles to promote the development of green chemistry and realize the sustainability of fine chemical industry.

[0003] As a new green synthesis strategy, electrocatalytic reduction technology has gradually become a research hotspot in recent years. Compared with traditional chemical catalytic hydrogenation, it has obvious advantages: the reaction conditions are mild, and it can be carried out at room temperature and pressure, which avoids the safety risks brought by high temperature and high pressure from the root; it can directly utilize renewable energy such as solar energy and wind energy to drive the reaction, effectively reducing carbon footprint and meeting the concept of low-carbon development; it does not need to add additional reducing agent, and can directly use water or proton source to complete the reduction process, eliminating the safety hazards of hydrogen storage and transportation; it has high selectivity and controllability, and by optimizing the electrode potential and catalyst structure, it can precisely inhibit side reactions and greatly improve the selectivity of the target product. These advantages make electrocatalytic reduction open up a new path for the sustainable synthesis of aromatic amines.

[0004] In the electrocatalytic process, the catalyst is the core component, and its performance directly determines the production efficiency and selectivity of the product. Among them, foamed metal-based materials have outstanding performance advantages in electrocatalytic reactions due to their high specific surface area, excellent electrical conductivity and three-dimensional interconnected structure. In particular, foamed metals based on 3d transition metals such as Fe, Co and Ni have a wide application prospect in the field of electrocatalytic organic conversion due to their rich electronic structure and controllable redox properties.

[0005] However, the existing foamed metal material has a single surface structure and a small number of active sites, resulting in low catalytic reduction efficiency of aromatic nitrile and easy occurrence of side reactions (such as over-hydrogenation to generate secondary or tertiary amines), low selectivity of the target product aromatic amine; at the same time, after multiple cycles of reaction, the performance of the catalyst is significantly attenuated, which cannot meet the continuous production requirements. In addition, the existing modification methods of foamed metal rely on complex doping, loading or high temperature and high pressure treatment process, which not only requires high equipment and high production cost, but also is difficult to realize industrialization and scale-up application.

[0006] Therefore, in-depth research on 3D transition metal-based foamed metal catalysts and their application in the process of electrocatalytic reduction of aromatic nitrile to prepare aromatic amine not only helps to explore an efficient and low-cost catalyst design method, but also further promotes the application of green electrocatalytic synthesis technology in organic chemistry, and provides a new solution for the sustainable preparation of fine chemicals. SUMMARY

[0007] In order to solve the problems of insufficient activity, low selectivity and poor stability of the foamed metal catalyst in the reaction of electrocatalytic reduction of aromatic nitrile to prepare aromatic amine, and the complex operation, high cost and difficulty in large-scale production of traditional modification methods, the present application provides a modification method of foamed metal, which realizes the precise regulation of the surface structure and electronic state of foamed metal through the two-step synergistic regulation of calcination-electroreduction, so that the modified foamed metal forms a nanosheet surface structure with high specific surface area, exposes more active sites, and optimizes the electron transfer efficiency, thereby exhibiting excellent electrocatalytic activity, high selectivity and good stability, and can efficiently catalyze the electroreduction of aromatic nitrile to prepare aromatic amine.

[0008] In order to achieve the purpose, the technical scheme is as follows: The present application provides a modification method of foamed metal, comprising the following steps: A) Calcination treatment of foamed metal One or more of foamed iron, foamed cobalt, foamed nickel, foamed copper, foamed zinc, foamed nickel-copper, foamed nickel-cobalt or foamed nickel-iron is selected as the base material, and is subjected to programmed temperature calcination in air or an oxygen-containing atmosphere. During the calcination process, the heating rate is controlled at 0.1-20 ℃ / min, and after being raised to 200-800 ℃, it is kept for 2-12 h, so as to induce lattice reconstruction of the metal surface through high-temperature oxidation, and form a nanoscale protruding structure with high specific surface area.

[0009] B) Constant potential electrochemical reduction of the calcined foamed metal The foamed metal treated in step A) is used as the working electrode, a platinum sheet is used as the counter electrode, and Hg / HgO is used as the reference electrode, which is placed in an alkaline electrolyte with a concentration of 0.1-5 mol / L, and is subjected to constant potential electrochemical reduction at-0.1--1Vvs. The electrochemical reduction is carried out under a constant potential condition of RHE (relative to a standard hydrogen electrode), and the reduction time is 5-300 min. The process can reduce the surface oxide layer into a metal element or an alloy, and introduce defect active sites through potential regulation, thereby significantly improving the electrocatalytic performance of the material.

[0010] In the modification method, the calcination step realizes the directional regulation of the surface morphology through the synergistic effect of the atmosphere and the temperature, and the subsequent constant potential reduction precisely optimizes the electronic structure, so that the number of active sites of the foam metal is significantly increased, thereby laying a foundation for efficient electrocatalytic reaction.

[0011] The application also provides a method for preparing aromatic amines by electrocatalytic reduction of aromatic nitriles based on the modified foam metal. An electrolysis reaction device is constructed by adopting a three-electrode system: the modified foam metal prepared by the modification method is used as a working electrode, a platinum sheet is used as a counter electrode, and Hg / HgO is used as a reference electrode; the cathode chamber and the anode chamber of the electrolytic cell are separated by a cation exchange membrane, an aromatic nitrile compound is added to the electrolyte solution in the cathode chamber, and a constant potential electrolysis method is used for electrolysis to generate an aromatic amine compound.

[0012] Preferably, the electrolyte solution is an alkali solution with a concentration of 0.1-5 mol / L, and the alkali solution contains 10-50 vol% of 1,4-dioxane. The ratio can optimize the adsorption behavior of the aromatic nitrile on the electrode surface and inhibit the occurrence of side reactions. The voltage of the electrolysis process is preferably controlled in the range of-0.1~-0.7 V vs RHE (relative to a standard hydrogen electrode). This potential range can efficiently drive the cyanide reduction reaction and reduce the hydrogen evolution reaction and other competitive reactions. The aromatic nitrile compound is preferably one or more of benzonitrile, 2-methylbenzonitrile, 3-methylbenzonitrile, 4-methylbenzonitrile, 2-chlorobenzonitrile, 2-fluorobenzonitrile, 4-bromobenzonitrile, 3-methoxybenzonitrile, 4-hydroxybenzonitrile, 3-aminobenzonitrile, and 4-cyanobenzoic acid. The method exhibits excellent catalytic reduction performance for the above-mentioned substrates.

[0013] The method for preparing aromatic amines realizes efficient conversion of aromatic nitriles to aromatic amines by precisely matching the high active sites of the modified foam metal with the reaction parameters, and has the characteristics of mild reaction conditions, high selectivity, and environmental friendliness.

[0014] Compared with the prior art, the application has the following advantages: 1. The modified method of foamed metal and the method of electrocatalytic preparation of aromatic amines based on the modified material, the core of which is to realize the performance improvement through the two-step synergistic process of calcination-constant potential electrochemical reduction. Specifically, the foamed metal is first calcined, and the high-temperature oxidation drives the precise structure reconstruction of the surface, which not only can regulate the crystal arrangement and the surface oxidation state, but also can significantly increase the surface roughness, thereby constructing a large number of catalytically active sites on the material surface; then, the calcined foamed metal is subjected to constant potential electrochemical reduction, which can not only efficiently reduce the oxidized metal to a highly active metal element or alloy, but also can further optimize the electronic structure of the material through potential regulation, thereby fundamentally improving the catalytic activity and long-term stability of the catalyst. The modified method of foamed metal has the following technical advantages: simple and easy operation process, no need for complex equipment support, widely available and low-cost foamed metal raw materials, suitable for large-scale industrial production needs, and wide commercial application prospects.

[0015] 2. The method of electrocatalytic reduction of aromatic nitriles to prepare aromatic amines further provides the modified foamed metal as the core catalyst, which can efficiently catalyze the reduction reaction of aromatic nitriles: not only has outstanding catalytic activity, but also has excellent stability and can maintain high-efficiency catalytic state for a long time. The method can be applied to the electrocatalytic preparation of various aromatic amines, and provides a highly potential solution for the green and sustainable production of aromatic amines. BRIEF DESCRIPTION OF DRAWINGS

[0016] Figure 1 The scanning electron microscope picture of the modified foamed nickel-cobalt electrode prepared in Example 1 of the present application; Figure 2 The high-resolution transmission electron microscope picture of the modified foamed nickel-cobalt electrode prepared in Example 1 of the present application; Figure 3 The curve graph of the change of the concentration of benzonitrile and benzylamine with the electric charge in the process of the electro-reduction reaction of benzonitrile catalyzed by the modified foamed nickel-cobalt electrode prepared in Example 1 of the present application; Figure 4 The corresponding relationship between the conversion rate of benzonitrile, the selectivity of benzylamine and the Faraday efficiency and the cycle number of the modified foamed nickel-cobalt electrode prepared in Example 1 of the present application in 20 cycle reactions; Figure 5The modified foam nickel-cobalt electrode prepared in Example 1 of the present application catalyzes the electro-reduction of 11 kinds of aromatic nitriles (including benzonitrile, 2-methylbenzonitrile, 3-methylbenzonitrile, 4-methylbenzonitrile, 2-chlorobenzonitrile, 2-fluorobenzonitrile, 4-bromobenzonitrile, 3-methoxybenzonitrile, 4-hydroxybenzonitrile, 3-aminobenzonitrile, and 4-cyanobenzoic acid), and a comparison chart of the conversion rate of the reactant aromatic nitrile, the selectivity of the product aromatic amine, and the Faraday efficiency is shown in the following table: Figure 6 The modified foam cobalt electrode prepared in Example 2 of the present application catalyzes the electro-reduction of benzonitrile, and a graph of the change of the concentration of benzonitrile and benzylamine with the electric charge during the reaction is shown in the following table: Figure 7 The modified foam copper electrode prepared in Example 3 of the present application catalyzes the electro-reduction of benzonitrile, and a graph of the change of the concentration of benzonitrile and benzylamine with the electric charge during the reaction is shown in the following table: Figure 8 The modified foam nickel-copper electrode prepared in Example 4 of the present application catalyzes the electro-reduction of benzonitrile, and a graph of the change of the concentration of benzonitrile and benzylamine with the electric charge during the reaction is shown in the following table. DETAILED DESCRIPTION

[0017] In order to further understand the present application, the preferred embodiments of the present application are described below in conjunction with the examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present application, and are not limitations on the claims of the present application.

[0018] In view of the demand for the electro-catalytic activity of the foam metal in the prior art, the present application provides a modification method of the foam metal, which is obtained by calcining and electrochemically reducing the foam metal, so that the surface of the foam metal is restructured to obtain a material with high catalytic reduction activity of aromatic nitriles. Specifically, the present application discloses a modification method of the foam metal, which comprises the following steps: A) calcining the foam metal; B) placing the foam metal obtained in step A) in an electrolyte and electrochemically reducing it at a constant potential to obtain a modified foam metal.

[0019] In the modification process of the foamed metal: the foamed metal is first calcined in the present application. The foamed metal is a conventional commercially available foamed metal material, and one or more of foamed iron, foamed cobalt, foamed nickel, foamed copper, foamed zinc, foamed nickel-copper, foamed nickel-cobalt and foamed nickel-iron can be selected. From the perspective of optimizing catalytic activity, one or more of foamed iron, foamed cobalt, foamed copper, foamed nickel-copper, foamed nickel-cobalt and foamed nickel-iron is preferred, and one or more of foamed cobalt, foamed copper, foamed nickel-cobalt and foamed nickel-copper is further preferred. The calcination process uses a method of heating first and then holding in an air or oxygen-containing atmosphere, and can be carried out in an air atmosphere or pure oxygen atmosphere. From the perspective of operation convenience and cost, the calcination is more preferably completed in an air atmosphere. The calcination temperature is controlled at 200-800℃, and from the perspective of surface reconstruction effect and energy balance, it is preferably 200-600℃, and further preferably 300-450℃. The heating rate of calcination is 0.1-20℃ / min, and in actual operation, it is preferably 1-10℃ / min, and more preferably 2-5℃ / min. The holding time of calcination is 2-12h, and from the perspective of efficiency and effect, it is specifically preferably 2-6h, and further preferably 2-4h.

[0020] After calcination is completed, the treated foamed metal is subjected to constant potential electrochemical reduction in the present application to obtain a modified foamed metal. The constant potential electrochemical reduction uses a conventional three-electrode system operation in the art, and the reduction potential is controlled at -0.1~-1V vs. RHE, and from the perspective of reduction efficiency and activity regulation, it is specifically preferably -0.2~-0.6V vs. RHE, and further preferably -0.2~-0.4V vs. RHE. The electrolyte used in the electrochemical reduction is 0.1-5mol / L of alkali solution, specifically 0.5-2mol / L of alkali solution, and further preferably 1mol / L of NaOH solution. The time of constant potential reduction is 5-300min, and in actual operation, it is preferably 10-180min, and more preferably 20-60min.

[0021] In the present application, the core role of the calcination step is to drive the directional reconstruction of the foamed metal surface through high temperature, significantly improve the specific surface area, and thereby expose more active sites for electrochemical reaction; at the same time, the calcination process is accompanied by surface oxidation reaction, which generates a corresponding thin layer of metal oxide on the surface of the foamed metal, laying a foundation for subsequent electronic structure regulation. The subsequent constant potential electrochemical reduction step not only can efficiently reduce the surface oxide layer to metal or alloy state, but also can optimize the material electronic structure through precise potential regulation, and finally realize the synergistic improvement of the catalytic activity and stability of the catalyst.

[0022] The present application also provides a method for preparing aromatic amines using the modified foamed metal described above, comprising the following steps: The modified foam metal prepared by the modification method is used as a working electrode, a platinum sheet is used as a counter electrode, and Hg / HgO is used as a reference electrode to construct an electrolysis reaction device in a three-electrode system. The cathode chamber and the anode chamber of the electrolysis cell are separated by a cation exchange membrane, and an aromatic nitrile compound is added to the electrolyte solution in the cathode chamber. A constant potential electrolysis method is used for electrolysis to generate an aromatic amine compound. The electrolyte solution is 0.1-5 mol / L of lye (containing 10-50 vol% of 1,4-dioxane), and 0.5-2 mol / L of lye (containing 10-40 vol% of 1,4-dioxane) is specifically preferred from the balance between reaction efficiency and substrate solubility, and 1 mol / L of NaOH solution (containing 10-40 vol% of 1,4-dioxane) is further preferred. The voltage of the electrolysis process is-0.1 to-0.7 V vs. RHE vs , and-0.2 to-0.5 V vs. RHE is specifically preferred in combination with product selectivity and energy consumption optimization vs , and-0.25 to-0.35 V vs. RHE is further preferred vs . The aromatic nitrile compound includes one or more of benzonitrile, 2-methylbenzonitrile, 3-methylbenzonitrile, 4-methylbenzonitrile, 2-chlorobenzonitrile, 2-fluorobenzonitrile, 4-bromobenzonitrile, 3-methoxybenzonitrile, 4-hydroxybenzonitrile, 3-aminobenzonitrile, and 4-cyanobenzoic acid, and one or more of benzonitrile, 2-methylbenzonitrile, 3-methylbenzonitrile, 4-methylbenzonitrile, 3-methoxybenzonitrile, 4-hydroxybenzonitrile, and 3-aminobenzonitrile is specifically preferred from the perspective of reaction conversion rate and applicability, and one or more of benzonitrile, 2-methylbenzonitrile, 3-methylbenzonitrile, and 4-methylbenzonitrile is further preferred. The method can efficiently realize the directional conversion of aromatic nitriles to aromatic amines through the synergistic effect of the high-activity catalytic sites of the modified foam metal and the reaction system, and has mild reaction conditions and high selectivity, and is suitable for the green preparation of various aromatic amines.

[0023] The preparation method of the modified foam metal provided by the application realizes the precise regulation of the surface structure and the electronic structure of the foam metal through a two-step synergistic process of calcination and electro-reduction, and finally obtains an electrode material with high catalytic activity and good stability. The preparation method has the advantages of simple operation, strong controllability of parameters, low cost of raw materials, easy scale-up production, and is suitable for commercialization and application, and provides a feasible scheme for the preparation of a foam metal electrode with high electro-catalytic activity.

[0024] Experimental data fully validated the technical effects of this invention: the modified nickel-cobalt foam electrode prepared by the method provided by this invention exhibits significant surface reconstruction, a substantial increase in roughness, and a significant increase in specific surface area, providing abundant active sites for electrocatalytic reactions. Using this modified nickel-cobalt foam electrode as the working electrode in a specific reaction system (with Hg / HgO as the reference electrode, a platinum sheet as the counter electrode, and the electrolyte being a 1 mol / L NaOH solution containing 10 mmol / L aromatic nitriles, of which 1,4-dioxane accounts for 10-40 vol%), at -0.28V... vs. Constant potential electrolysis at RHE potential can efficiently convert aromatic nitriles into aromatic amines with excellent reaction performance—the conversion rate of aromatic nitriles exceeds 90%, the selectivity of the target product aromatic amines is higher than 90%, and the Faraday efficiency is greater than 60%, which fully demonstrates the outstanding advantages of the method of this invention in the electrocatalytic reduction of aromatic nitriles to prepare aromatic amines.

[0025] To facilitate a further understanding of the present invention, the following detailed description of the modification method of foam metal and the preparation method of aromatic amines provided by the present invention is provided in conjunction with specific embodiments. It should be noted that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of protection of the present invention.

[0026] All raw materials used in this invention are not subject to any special restrictions on their source or purity, and are all conventional products that are available on the market. Considering the stability of the reaction effect, it is preferable to use raw materials of analytical grade or conventional purity commonly used in the field of electrocatalytic preparation.

[0027] To facilitate the differentiation of different types of modified foam metal electrodes and simplify the description, this invention adopts "M-ER" as a unified identifier for modified foam metal electrodes, where "M" represents the type of foam metal (e.g., Co represents cobalt foam, Cu represents copper foam, NiCo represents nickel-cobalt foam alloy, etc.), and "ER" (abbreviation for Electroreduction) indicates that the electrode has undergone electrochemical reduction treatment.

[0028] Example 1 Preparation and electrocatalytic performance verification of modified nickel-cobalt foam electrodes: A) Preparation method of modified nickel-cobalt foam electrode (NiCo-ER) (1) Cut the foamed nickel-cobalt into 1×3cm pieces. 2 The sample is placed in a calcining furnace and heated to 450°C at a heating rate of 5°C / min in an air atmosphere. It is then held at that temperature for 2 hours and allowed to cool naturally to complete the calcination process. (2) Construction of three-electrode system: using the calcined foam nickel-cobalt as cathode, platinum plate as counter electrode, Hg / HgO electrode as reference electrode, the two electrodes of electrolytic cell were separated by cation exchange membrane. The above electrodes were immersed in 1 mol / L NaOH electrolyte, and constant potential reduction was carried out at-0.28 V vs. RHE for 20 min, to obtain modified foam nickel-cobalt electrode, recorded as NiCo-ER.

[0029] B) Application of electrocatalytic reduction of aromatic nitrile to prepare aromatic amine (1) Construction of reaction system: using NiCo-ER as working electrode, Hg / HgO electrode as reference electrode, platinum plate as counter electrode; the electrolyte was 1 mol / L NaOH solution containing 10 mmol / L aromatic nitrile (containing 10-40 vol% of 1,4-dioxane). Among them, the aromatic nitrile was one or more of benzonitrile, 2-methylbenzonitrile, 3-methylbenzonitrile, 4-methylbenzonitrile, 2-chlorobenzonitrile, 2-fluorobenzonitrile, 4-bromobenzonitrile, 3-aminobenzonitrile, 4-cyanobenzoic acid, 3-methoxybenzonitrile and 4-hydroxybenzonitrile (the corresponding 1,4-dioxane concentration in the used electrolyte was 10 vol%, 30 vol%, 30 vol%, 30 vol%, 30 vol%, 30 vol%, 30 vol%, 30 vol%, 30 vol%, 20 vol%, 20 vol%, respectively).

[0030] (2) Electrolysis reaction: electrolysis was carried out at-0.28 V vs. RHE until the transferred charge reached 90 C, to obtain the corresponding aromatic amine product.

[0031] The NiCo-ER electrode prepared in Example 1 showed excellent electrocatalytic activity, selectivity and stability in the electrocatalytic reduction of aromatic nitrile reaction, as follows.

[0032] Surface morphology analysis: scanning electron microscope (SEM) Figure 1 ) showed that after calcination-electroreduction treatment, the surface roughness of NiCo-ER electrode increased significantly, and a large number of nanosheet cross-linked structures were generated, which could significantly increase the number of active site exposure and provide structural basis for efficient catalysis; high-resolution transmission electron microscope (HRTEM) Figure 2 ) confirmed that the modified NiCo-ER electrode maintained the NiCo alloy structure, and the interplanar spacing was consistent with that of NiCo alloy, indicating that the alloy framework was not destroyed during the electroreduction process.

[0033] Benzonitrile reduction performance: Figure 3 The curve of the concentration of benzonitrile and benzylamine with the change of charge in the process of the electroreduction reaction of benzonitrile catalyzed by the NiCo-ER electrode prepared in Example 1; from Figure 3It can be seen that the concentration of benzonitrile gradually decreases with the increase of charge amount, and the concentration of benzylamine increases synchronously. When the transferred charge amount reaches 90C, the conversion rate of benzonitrile reaches 93.8%, the selectivity of benzylamine reaches 99.4%, and the faradic efficiency is 67.3%, indicating that the NiCo-ER can efficiently catalyze the directional conversion of benzonitrile to benzylamine.

[0034] Cyclic stability verification: The cyclic stability of the NiCo-ER electrode prepared in Example 1 for the electrocatalytic reduction of benzonitrile to prepare benzylamine was detected. After 20 cycles of testing (the specific process is as follows: Figure 4 ), the conversion rate of benzonitrile, the selectivity of benzylamine and the faradic efficiency of the NiCo-ER electrode did not decrease significantly, which proved that it had excellent durability and could meet the needs of continuous production.

[0035] The performance of the NiCo-ER electrode prepared in Example 1 for the electrocatalytic reduction of various aromatic nitriles to prepare aromatic amines was detected: the reduction results (the specific process is as follows: Figure 5 ) of 11 kinds of aromatic nitriles (including benzonitrile, 2-methylbenzonitrile, 3-methylbenzonitrile, 4-methylbenzonitrile, 2-chlorobenzonitrile, 2-fluorobenzonitrile, 4-bromobenzonitrile, 3-methoxybenzonitrile, 4-hydroxybenzonitrile, 3-aminobenzonitrile, and 4-cyanobenzoic acid) showed that the NiCo-ER electrode exhibited high catalytic performance for substrates containing methyl, halogen, methoxy, hydroxyl and other substituents: the conversion rate of all substrates was > 90%, the selectivity of the target amine product was > 90%, and the faradic efficiency was > 60%, which embodied the wide substrate applicability.

[0036] The NiCo-ER electrode prepared in this example realizes the synergistic optimization of structure and performance through "calcination-electroreduction" modification, and exhibits high activity, high selectivity, high stability and wide substrate applicability in the electrocatalytic reduction of aromatic nitriles to prepare aromatic amines, which verifies the effectiveness of the modification method of the present application.

[0037] Example 2 Preparation of modified cobalt foam electrode and verification of its electrocatalytic performance: A) Preparation of modified cobalt foam electrode (Co-ER) The same operation process as Example 1 was adopted to modify the foam cobalt, which specifically included: the foam cobalt was cut into 1×3 cm 2 specifications, calcined at 450℃ (heating rate 5℃ / min, holding for 2h), and then reduced at-0.28V vs. RHE constant potential in 1 mol / L NaOH electrolyte for 20 min to obtain the modified foam cobalt electrode, which was denoted as Co-ER.

[0038] B) Application of electrocatalytic reduction of benzonitrile to prepare benzylamine The reaction system construction and operating parameters were consistent with those in Example 1, except that benzonitrile was used as the aromatic nitrile substrate: Co-ER was used as the working electrode, Hg / HgO as the reference electrode, a platinum sheet as the counter electrode, and the electrolyte was a 1 mol / L NaOH solution containing 10 mmol / L benzonitrile (containing 10 vol% 1,4-dioxane), at -0.28V. vs. RHE was electrolyzed at a constant potential until the transferred charge reached 90C.

[0039] The Co-ER electrode prepared in Example 2, after being modified by "calcination-electroreduction", exhibited excellent performance in the electrocatalytic reduction reaction of benzonitrile: like Figure 6 As shown in the concentration-charge curve of benzonitrile reduction catalyzed by the Co-ER electrode, the benzonitrile concentration continuously decreases with increasing charge, while the anitoline concentration increases synchronously. When the transferred charge reaches 90C, the benzonitrile conversion rate reaches 94.7%, the anitoline selectivity is 97.7%, and the Faraday efficiency is 65.2%. These results indicate that the modified cobalt foam electrode can efficiently catalyze the directional conversion of benzonitrile to anitoline, further verifying that the modification method of this invention is universally applicable to different types of foam metals and can effectively improve their electrocatalytic performance.

[0040] Example 3 Preparation of modified copper foam electrode and verification of its electrocatalytic performance: A) Preparation of modified copper foam electrode (Cu-ER) Using the same operating procedure as in Example 1, modified copper foam was performed on the substrate, specifically including: cutting the copper foam into 1×3cm pieces. 2 Specifications: After calcination at 450℃ (heating rate 5℃ / min, holding time 2h), it is reacted in a 1mol / L NaOH electrolyte at -0.28V. vs. After RHE constant potential reduction for 20 min, a modified copper foam electrode was obtained, denoted as Cu-ER.

[0041] B) Application of electrocatalytic reduction of benzonitrile to prepare benzylamine The reaction system construction and operating parameters were consistent with those of Example 1, except that benzonitrile was used as the aromatic nitrile substrate: Cu-ER was used as the working electrode, Hg / HgO as the reference electrode, a platinum sheet as the counter electrode, and the electrolyte was a 1 mol / L NaOH solution containing 10 mmol / L benzonitrile (containing 10 vol% 1,4-dioxane), at -0.28V. vs. RHE was electrolyzed at a constant potential until the transferred charge reached 90C.

[0042] The Cu-ER electrode prepared in Example 3, after being modified by "calcination-electroreduction", exhibited excellent performance in the electrocatalytic reduction reaction of benzonitrile. like Figure 7 As shown in the concentration-charge curve of benzonitrile reduction catalyzed by the Cu-ER electrode, the benzonitrile concentration continuously decreases with increasing charge, while the anitoline concentration increases synchronously. When the transferred charge reaches 90°C, the benzonitrile conversion rate reaches 96.4%, the anitoline selectivity is 91.7%, and the Faraday efficiency is 63.2%. These results demonstrate that the modified copper foam electrode can efficiently catalyze the directional conversion of benzonitrile to anitoline, further verifying the universality of the modification method of this invention for different types of foam metals and its ability to effectively improve their electrocatalytic performance.

[0043] Example 4 Preparation and electrocatalytic performance verification of modified nickel-copper foam electrode: A) Preparation of modified nickel-copper foam electrode (NiCu-ER) Using the same operating procedure as in Example 1, modified nickel-copper foam was performed as the substrate, specifically including: cutting the nickel-copper foam into 1×3cm pieces. 2 Specifications: After calcination at 450℃ (heating rate 5℃ / min, holding time 2h), it is reacted in a 1mol / L NaOH electrolyte at -0.28V. vs The modified nickel-copper foam electrode, denoted as NiCu-ER, was obtained by constant potential reduction with RHE for 20 min.

[0044] B) Application of electrocatalytic reduction of benzonitrile to prepare benzylamine The reaction system construction and operating parameters were consistent with those in Example 1, except that benzonitrile was used as the aromatic nitrile substrate: NiCu-ER was used as the working electrode, Hg / HgO as the reference electrode, a platinum sheet as the counter electrode, and the electrolyte was a 1 mol / L NaOH solution containing 10 mmol / L benzonitrile (containing 10 vol% 1,4-dioxane), at -0.28V. vs .RHE was electrolyzed at a constant potential until the transferred charge reached 120C.

[0045] The NiCu-ER electrode prepared in Example 4 exhibited excellent performance in the electrocatalytic reduction reaction of benzonitrile: like Figure 8 As shown in the concentration-charge curve of benzonitrile reduction catalyzed by the NiCu-ER electrode, the benzonitrile concentration continuously decreases with increasing charge, while the aniline concentration increases synchronously. When the transferred charge reaches 120°C, the benzonitrile conversion rate reaches 91.5%, the aniline selectivity is 98.6%, and the Faraday efficiency is 54.3%. These results demonstrate that the modified foamed nickel-copper electrode can efficiently catalyze the directional conversion of benzonitrile to aniline, further verifying the universality of the modification method of this invention for different types of foamed metals and its ability to effectively improve their electrocatalytic performance.

[0046] The above description of the embodiments is only used to help understand the method of the present application and its core idea. It should be noted that, for those skilled in the art, some improvements and modifications can be made to the present application without departing from the principles of the present application, and these improvements and modifications also fall within the protection scope of the claims of the present application.

Claims

1. A method for modifying a foamed metal, comprising the steps of: A) calcining the foamed metal; B) subjecting the foamed metal obtained in step A) to electrochemical reduction in an electrolyte solution at a constant potential to obtain a modified foamed metal.

2. The modification method according to claim 1, characterized by, The foamed metal is selected from one or more of foamed iron, foamed cobalt, foamed nickel, foamed copper, foamed zinc, foamed nickel-copper, foamed nickel-cobalt and foamed nickel-iron.

3. The modification method of claim 1, wherein, The calcination is performed in air or an oxygen-containing atmosphere.

4. The modification method of claim 1, wherein, The temperature of the calcination is 200-800°C; the heating rate of the calcination is 0.1-20°C / min; and the holding time of the calcination is 2-12h.

5. The modification method of claim 1, wherein The constant potential is -0.1~ -1V vs. RHE (relative to standard hydrogen electrode); the electrolyte is 0.1~5 mol / L of alkali solution; the time for electrochemical reduction under constant potential is 5~300 min.

6. A modified foamed metal obtained by the method of any one of claims 1-5.

7. A method of electrocatalytic reduction of aromatic nitrile to produce aromatic amine, characterized by: Aromatic amine compounds are obtained by adding aromatic nitrile compounds to an electrolyte solution and performing electrolysis by constant potential electrolysis using the modified foamed metal of claim 6 as the working electrode.

8. The method of claim 7, wherein, The electrolyte solution is an alkali solution of 0.1-5 mol / L containing 10-50 vol% of 1,4-dioxane.

9. The method of claim 7, wherein, The voltage of the electrolysis is -0.1 to -0.7 V vs. RHE.

10. The method of claim 7, wherein, The aromatic nitrile compounds are one or more of benzonitrile, 2-methylbenzonitrile, 3-methylbenzonitrile, 4-methylbenzonitrile, 2-chlorobenzonitrile, 2-fluorobenzonitrile, 4-bromobenzonitrile, 3-methoxybenzonitrile, 4-hydroxybenzonitrile, 3-aminobenzonitrile and 4-cyanobenzoic acid.